2015
DOI: 10.1073/pnas.1421917112
|View full text |Cite
|
Sign up to set email alerts
|

Environmental stress induces trinucleotide repeat mutagenesis in human cells

Abstract: The dynamic mutability of microsatellite repeats is implicated in the modification of gene function and disease phenotype. Studies of the enhanced instability of long trinucleotide repeats (TNRs)-the cause of multiple human diseases-have revealed a remarkable complexity of mutagenic mechanisms. Here, we show that cold, heat, hypoxic, and oxidative stresses induce mutagenesis of a long CAG repeat tract in human cells. We show that stress-response factors mediate the stress-induced mutagenesis (SIM) of CAG repea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
35
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 57 publications
1
35
0
Order By: Relevance
“…Previously, we showed that four different environmental stresses—cold, heat, hypoxic and oxidative—induce trinucleotide repeat (TNR) mutagenesis in human cells via a pathway that involves stress response factors (SRF’s) and DNA rereplication [1]. Other pathways known to modulate TNR instability—transcription, mismatch repair, nucleotide excision repair, and base excision repair—are not involved in environmental stress-induced TNR mutagenesis, consistent with the known repression of these processes during stress [15].…”
mentioning
confidence: 75%
See 3 more Smart Citations
“…Previously, we showed that four different environmental stresses—cold, heat, hypoxic and oxidative—induce trinucleotide repeat (TNR) mutagenesis in human cells via a pathway that involves stress response factors (SRF’s) and DNA rereplication [1]. Other pathways known to modulate TNR instability—transcription, mismatch repair, nucleotide excision repair, and base excision repair—are not involved in environmental stress-induced TNR mutagenesis, consistent with the known repression of these processes during stress [15].…”
mentioning
confidence: 75%
“…Other pathways known to modulate TNR instability—transcription, mismatch repair, nucleotide excision repair, and base excision repair—are not involved in environmental stress-induced TNR mutagenesis, consistent with the known repression of these processes during stress [15]. The mechanism by which the stress response and DNA rereplication bring about TNR mutagenesis remains unclear.…”
mentioning
confidence: 79%
See 2 more Smart Citations
“…Studies of TNR instability in model organisms—bacteria, yeast, mammals, and human cells—shed light on the spectrum of DNA metabolic processes at play in expanded repeats, including replication, transcription, DNA repair, genome wide demethylation, and rereplication [11-19]. We previously showed that transcription across long CAG repeats induces repeat instability in human cells and defined the modulating role of DNA repair factors in this process [14, 20].…”
Section: Introductionmentioning
confidence: 99%